2015
DOI: 10.1063/1.4919387
|View full text |Cite
|
Sign up to set email alerts
|

(100)-Textured KNN-based thick film with enhanced piezoelectric property for intravascular ultrasound imaging

Abstract: Using tape-casting technology, 35 m free-standing (100)-textured Li doped KNN (KNLN) thick film was prepared by employing NaNbO (NN) as template. It exhibited similar piezoelectric behavior to lead containing materials: a longitudinal piezoelectric coefficient (d) of ∼150 pm/V and an electromechanical coupling coefficient ( ) of 0.44. Based on this thick film, a 52 MHz side-looking miniature transducer with a bandwidth of 61.5% at -6 dB was built for Intravascular ultrasound (IVUS) imaging. In comparison with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…It was reported that 35 µm free‐standing (100)‐textured Li‐doped KNN thick film was prepared by employing NaNbO 3 as the template. The film exhibited higher longitudinal d 33 of 150 pm V −1 and k t of 0.44 than any other KNN thick films, and are comparable to PZT‐based films . Meanwhile, Fu et al .…”
Section: Synthetic Techniquesmentioning
confidence: 85%
See 2 more Smart Citations
“…It was reported that 35 µm free‐standing (100)‐textured Li‐doped KNN thick film was prepared by employing NaNbO 3 as the template. The film exhibited higher longitudinal d 33 of 150 pm V −1 and k t of 0.44 than any other KNN thick films, and are comparable to PZT‐based films . Meanwhile, Fu et al .…”
Section: Synthetic Techniquesmentioning
confidence: 85%
“…The output energy is almost the same between KNN‐based f‐PEH and PZT‐based f‐PEH, while the eluted Pb concentration from the PZT is about three orders of magnitude higher than the Nb concentration from the KNN, as shown in Figure a, and the Pb levels in those fluids are not acceptable. Zhou's group from the Department of Biomedical Engineering of University of Southern California, has developed a KNN‐film‐based high‐frequency transducer and has applied it to intravascular ultrasound (IVUS) imaging that plays a crucial role in diagnosing coronary artery disease . Figure d is the photo of the needle IVUS transducer and Figure e compared the IVUS imaging result of KNN‐based transducer and PMN‐PT transducer.…”
Section: Application Of Knn Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al [36] found that the salt contributed to the conversion reaction from plate-like precursor to KNN or NaNbO 3 platelets. Zhu et al [37] fabricated Li-doped KNN thick film by employing NaNbO 3 as template. Compared to NaNbO 3 two-dimensional (2D) templates, KNN plate-like crystals are expected to possess high piezoelectric properties, and might be much similar to the ceramic matrix [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…For example, although computed tomography (CT) possesses the ability to detect calcium in plaque3, its detection is of limited physiological significance and vulnerable to plaque type. Similarly, although an intravascular ultrasound (IVUS), which is a catheter-based intravascular imaging technique with good penetration depth and axial resolution, has been demonstrated to provide structural information of atherosclerotic plaque456, the contrast between the lipid-rich region and other soft tissue is confined789. To address this issue, intravascular photoacoustic (IVPA) imaging seems to be an alternative method to detect lipid pool and atherosclerotic calcification.…”
mentioning
confidence: 99%